GeoLife2.0: A Location-Based Social Networking Service - Zheng, Yu; Xie, Xing; Ma, Wei-Ying (Proceedings of the 10th International Conference on Mobile Data Management (MDM 2009), 2009)
GeoLife2.0 is a GPS-data-driven social networking service where people can share life experiences and connect to each other with their location histories. By mining people’s location history, GeoLife can measure the similarity between users and perform personalized friend recommendation for an individual. Later, we can predict the individual’s interest level in the locations visited by their friends while have not been found by them. The locations with relatively high interesting level can be recommended. Therefore, GeoLife2.0 can expand a user’s social network, provide them with a trustworthy resource matching their interests and help them sponsor geo-related activities like cycling with minimal effort.